2008
DOI: 10.4041/kjod.2008.38.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airway and tongue in facial morphology of prepubertal Class I, II children

Abstract: Fig 1.Landmarks and reference lines used in this study. Ar (Articulare), intersection between posterior cranial base surface and posterior border of condylar head and neck; Pt (Pterygoid point), the posterior point of the pterygopalatine fossa; ANS (anterior nasal spine), Anterior point of the maxilla; PNS (posterior nasal spine), Posterior point of the palatine bone; Me (Menton), the inferior point of the symphysis; Pm (Protuberance menti), the most superior point where the heavy cortical bone of the symphysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Our present study found that with an increase in PFH, the tongue area increases, which is in accordance with Hwang et al [11] Thus, our study concluded that facial height has an influence on tongue area [ Table 3].…”
Section: Discussionsupporting
confidence: 91%
“…Our present study found that with an increase in PFH, the tongue area increases, which is in accordance with Hwang et al [11] Thus, our study concluded that facial height has an influence on tongue area [ Table 3].…”
Section: Discussionsupporting
confidence: 91%
“…Abu Allhaija and Al-Khateeb 20 concluded that the anteroposterior skeletal pattern showed weak, but significant correlation with inferior PAS. Hwang et al 27 reported that a constricted nasopharyngeal airway is associated with detruded mandible and maxilla. These two previous studies were based on lateral cephalograms.…”
Section: Discussionmentioning
confidence: 98%
“…[24] The gonial angle has no significant role in the dimensions of the pharyngeal airway space and position of the tongue. The recent study by Hwang et al [25] showed that airway space measurements in low and neutral angle Class II subjects did not differ from those of the skeletal Class I control group, while in the high-angle groups upper airway space was significantly smaller. Ucar and Uysal [11] also found that vertical growth patterns, but not malocclusion type, influenced upper airway dimensions.…”
Section: Discussionmentioning
confidence: 85%